A spatiotemporal analysis of agricultural prices: An application to Colombian data (2013)
This study focusses on whether the geographical separation of markets constitutes a factor that helps explain the dynamics of agricultural prices. To do this, the authors employ a highly disaggregated dataset for Colombia that consists of weekly observations on wholesale prices for 18 agricultural products traded in markets scattered around the country. The sample period spans almost a decade. According to their results, which are based on generalized impulse response functions, distance (and thus transportation costs) is a factor that helps explain the speed at which prices adjust to shocks in other locations, thus confirming that price adjustments take longer for markets farther apart. © 2012 Wiley Periodicals, Inc.